(untitled) (Journal on studies and research of academic knowledge, 2022)
Epidemics caused by Rosellinia spp. are common in Colombia, causing cocoa crop losses. The aim was to evaluate alternative treatments for the management of soil diseases. An experiment was carried out in Palestina, Caldas, Colombia, on 4-year-old cocoa plants. The treatments were T1) Conventional management; T2) Foliar application of resistance inducers T3) Combination of T2 + Trichoderma spp.; T4) Bacillus subtillis + Trichoderma spp.; T5) Control. Tree severity was evaluated using a six-grade scale: G0 = healthy tree; G1 = chlorosis and yellowing of few leaves; G2 = 20% yellowing of leaves and apical buds; G3 = tree with 50% withered leaves; G4 = tree with 70% withered leaves; G5 = dead tree. For the statistical analysis, the observed categories were modeled with a multinomial distribution. The statistical model used was the cumulative logit with the treatments as the covariate and the parameters were estimated at a significance level of 5%. T2 showed that 93% of trees remained healthy, while with T3 14% of trees showed symptoms of chlorosis and yellowing of few leaves and 12% died, showing an increase in the progress of the disease. Treatments T1 and T4 showed similar probability values to the control (T5) for all categories, which could indicate that these treatments have a low response in disease control